Strategies for Strengthening Technology-Based Governance of Islamic Boarding School Libraries in the Digital Era - Erland Cahyo Saputro; Diska Aulia Rahman; Muhammad Himmatur Riza (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2026)
The rapid advancement of information technology requires Islamic boarding schools (pesantren) to modernize their library governance to enhance the quality of information services and students’ literacy. This community service program aimed to describe strategies for strengthening technology-based library governance in pesantren in the digital era. The study employed a descriptive qualitative approach using a service-learning model. The participants included pesantren leaders, library administrators, and students from several Islamic boarding schools in Semarang. The findings revealed that most pesantren libraries were still managed conventionally, lacked standardized operating procedures (SOPs), and made limited use of digital technology in collection management and library services. The intervention program consisted of training on shelving and collection classification, the utilization of library management applications, library space arrangement, and the development of a digital catalog. The evaluation results indicated that the program was effective, as evidenced by improved managerial and technical competencies among library administrators, the establishment of a simple digital catalog system, and enhanced accessibility and efficiency of information services for students. The program also generated positive impacts on library administrators through increased technical and managerial skills, while students benefited from more organized, accessible, and literacy-supportive library services. Based on these findings, strategies for strengthening technology-based library governance in pesantren can be implemented through systematic management planning, capacity building for human resources, the provision of technology-supporting facilities, and the sustainable implementation of digital library systems. Therefore, it is recommended that pesantren develop standardized operating procedures, expand integrated digital catalog systems, provide continuous training for library administrators, and strengthen literacy networks among pesantren to ensure the sustainability of the program.